PERAN STRATEGI BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK NASA DI STOCKIST NASA UNIT 2 TULANG BAWANG - Nursari, Pratiwi Retno; Suhada, Bambang; Riyanto, Kuncoro Budi (SIMPLEX: Journal of Economic Management, 2025)
This study aims to test and determine the impact of products, price influence, location influence, promotion influence, on the purchase decision of NASA products at Stockist Unit 2 Tulang Bawang Regency. The approach used in this research is a type of quantitative research, the data used in this research is secondary and obtained from a questionnaire or questionnaire distributed to consumers of NASA products at Stockist Nasa Unit 2 Tulang Bawang Regency. The sample was selected by giving questionnaires to people who were met and obtained 100 consumers as a research sample and then measured using a Likert scale. The data was processed using SPSS with multiple linear regression analysis. The results of this study are (1) Products have no impact on purchasing decisions, (2) Price has an effect on purchasing decisions, (3) location has no effect on purchasing decisions, (4) product promotion has an impact on purchasing decisions, (5) the results of the study show that product, price, location, and promotion simultaneously affect purchasing decisions for nasa products at stockiest nasa Tulang Bawang Regency